Central Nervous System Involvement in Chronic Obstructive Pulmonary Disease - Jumana Kareem; Ali Al-Hashimi; Hashim Al-Kadhimi (The Iraqi Journal of Medical Sciences)
Background: Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous disease. Studies evaluating both peripheral and central nervous system involvement in patients with COPD at the same time are rare. Transcranial magnetic stimulation (TMS) assesses excitability of the motor cortex and corticospinal pathway function. Diaphragmatic contractile function had been assessed by cortical and cervical magnetic stimulation of the phrenic nerve roots in COPD patients. Objective: To investigate electrophysiologically central nervous system involvement in COPD as compared to healthy controls, to study the central neural derive of the diaphragm by assessing TMS-MEP parameters of the phrenic nerve in patients with COPD and compare these with healthy controls. Methods: The present study is a case control study was conducted in Al-Imamein Al-Kadhimein Medical City, from November 2019 to October 2021 included 40 COPD patients and 40 healthy volunteers who were subjected to blood gas and biochemical analysis and pulmonary function test before commencement of neurophysiological analysis. Results: Statistically significant prolongation of the cortical motor latencies as well as peripheral motor conduction times of both phrenic nerves in COPD patients compared to control subjects (p<0.001). The means of the central motor conduction times in the both phrenic nerves were higher in COPD patients compared to controls, yet, the difference was only significant in the right phrenic nerve. There was statistically significant increase in the means of the motor threshold of both phrenic nerve in some patients with COPD in comparison with control group. The phrenic nerve cortical latencies showed the most sensitive and specific parameters to study the involvement of nervous system in COPD, while the peripheral motor conduction time was the second most sensitive and specific parameter. No correlations observed between body mass index, SpO2 with phrenic nerves TMS parameters. Conclusion: The central neuropathy is one of the complications in COPD patients. Motor threshold of phrenic nerves was significantly higher in COPD patients reflecting significant decrease in excitability of motor cortex affecting excitatory contact with subcortical neurons. Results of the cortical and radicular MEP latencies of both phrenic nerves were of high sensitivity and specificity in diagnosing nervous system involvement in COPD. Keywords: Chronic obstructive pulmonary disease, phrenic nerve, TMS Citation: Kareem JM, Al-Hashimi AF, Al-Kadhimi HM. Central nervous system involvement in chronic obstructive pulmonary disease. Iraqi JMS. 2023; 21(2): 224-236. doi: 10.22578/IJMS.21.2.10